DEVELOPMENT AND IMPLEMENTATION OF POCKETBOOK LEARNING MEDIA IN THE COST BUDGET PLAN SUBJECT AT SMKN 1 TUBAN - Vannia Aisha Putri Wahyudi; Gde Agus Yudha Prawira Adistana (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study was motivated by the need for practical learning media to help students understand the technical content of the Cost Budget Plan (RAB) subject in Grade XI of Building Modeling and Information Design (DPIB) at SMK Negeri 1 Tuban . Therefore, this study aimed to develop and implement a pocket book as a learning medium and to determine its feasibility, students' responses, and learning outcomes after its use. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were Grade XI DPIB students at SMK Negeri 1 Tuban , and data were collected through observation, questionnaires, learning outcome tests, as well as validation by material experts and media experts. The results showed that the pocket book learning media was feasible, with a material expert validation score of 88% and a media expert validation score of 81%. Teacher observation results reached 90%, while students' responses achieved 86%, categorized as very good. Students' learning outcomes showed a classical mastery level of 94% students achieving mastery. Thus, the pocket book is effective as a learning medium for the Cost Budget Plan (RAB) subject.